ANTEMORTEM DAN POSTMORTEM HEWAN KURBAN - Tri Ananda Erwin Nugroho; Muhammad Sayuti; Nirmawati Mohamad (xxxx-xxxx, 2022)
It has become a routine for Muslims at the time of Eid al-Adha to slaughter sacrificial animals. Slaughtered animals must be healthy because if they carry a disease that can be transmitted to humans (zoonosis) then the animal is not fit to be sacrificed. In anticipation of oral and nail diseases that have entered Indonesia and anthrax that has existed in Gorontalo Province in recent years, it is necessary to carry out antemortem and postmortem examinations of sacrificial animals. The location of the antemortem and postmortem was carried out in several mosques in Bonebolango Regency with a total of 34 sacrificial animals examined consisting of cattle. The results obtained during the antemortem examination found 1 cow had cachexia (thinness) of 2.9% and 33 cows were in normal condition. From the post-mortem examination of 34 sacrificial cows, 26.5% of pneumonia cases were found, consisting of 1 case of interlobular pneumonia and 8 cases of aspiration pneumonia, and 20.5% of distomatosis (liver worms).